Entrepreneurship education on entrepreneurial intention: The moderating role of the personality and family economic status - Liu, Yiran; Li, Min; Li, Xin; Zeng, Jingyi (Frontiers in Psychology, 2022)
This study investigates the effect of entrepreneurship education on college students’ entrepreneurial intentions, and moderating effects of personalities and family economic status on the relationship between entrepreneurship education and entrepreneurial intentions. We test our assumptions using a sample of college students in Tianjin in China and analyze the data of 326 questionnaires with validated measures of entrepreneurship education, entrepreneurial intentions, proactive personality, narcissistic personality and family economic status. The results show that entrepreneurship education positively affects entrepreneurial intentions of college students; proactive personality negatively moderates this relationship; family economic status positively moderates this relationship. However, the moderating effect of narcissistic personality has not been verified. This study is unique and innovative as it brings new insights to this stream of literature by introducing the roles of personalities and family economic status in the relationship between entrepreneurship education and entrepreneurial intentions.